How much social responsibility should firms assume and of which kind? Firms, governments and NGOs as alternative providers of social services - Lilac Nachum (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
This Perspective proposes that the provision of social services should be based on the characteristics of the inputs and outputs. Firms should provide only social services that are aligned with their core competencies and strategies and can generate proprietary benefits. Governments (and NGOs) should assume responsibility for other social services.
Keywords: 330